Peranan Promosi Dalam Melestarikan Gastronomi Sunda Berbasis Pangan Lokal - Sri Marini; Ita Karnita; Superwiratni Superwiratni (Universitas Bunda Mulia, 2025)
Food security and self-reliance are currently important issues. Global climate change has affected the stability of food production and supply. Likewise, war events that have an impact on food imports and procurement have made the government more concerned in this matter. Various efforts have been made to support food security and self-reliance. Indonesia is rich in local food sources, especially the city of Bandung which is geographically advantaged by natural conditions. This study aims to analyse the promotion carried out by Sundanese gastronomy actors and whether promotion through promotional tools used has an impact on preservation, how business and factors that influence the preservation of Sundanese gastronomy made from local food. The research approach used by researchers is to use a qualitative approach. The research method is Field research where research reveals the meaning given by community members to their behaviour and the surrounding reality. Key Informants in this study are internal informants from 3 Sundanese gastronomy culinary businesses, as well as external informants, namely 15 consumers of Sundanese gastronomy as eligible sources who provide information about the role of promotion and preservation efforts of each research object. The data analysis technique used in this research is qualitative data analysis which is carried out interactively through the data analysis process.